2014
DOI: 10.1002/jor.22739
|View full text |Cite
|
Sign up to set email alerts
|

Transsacral screw safe zone size by sacral segmentation variations

Abstract: Variations in sacral segmentation may preclude safe placement of transsacral screws for posterior pelvis fixation. We developed a novel automated 3D technique to determine the safe zone size for transsacral screws in the upper two sacral segments in 526 adult pelvis computed tomography scans. Safe zone sizes were then compared by gender and sacral segmentation variations (number of neuroforamen and the presence/absence of lumbosacral transitional vertebrae, AELSTV). Ten millimeters was used as the safety thres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
23
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 24 publications
2
23
0
Order By: Relevance
“…Using the largest 10-mm diameter cutoff, as reported by Gardner et al [8] and Moed and Geer [24], transsacral osseous corridors at the S1 and S2 vertebrae would have been too narrow in 36% and 26% of pelves compared with 32% and 12% when using the 9-mm cutoff. Measured cylindrical diameters in our study (S1, 13 ± 0.3 mm; S2, 12 ± 2 mm) are similar to those reported by Lee et al [19] (S1: 14 ± 4 mm; S2 11 ± 3 mm) and larger than those reported by Vanderschot et al [37]. (S1, 8 ± 0.9 mm; S2, 7 ± 3 mm).…”
Section: Discussionsupporting
confidence: 90%
“…Using the largest 10-mm diameter cutoff, as reported by Gardner et al [8] and Moed and Geer [24], transsacral osseous corridors at the S1 and S2 vertebrae would have been too narrow in 36% and 26% of pelves compared with 32% and 12% when using the 9-mm cutoff. Measured cylindrical diameters in our study (S1, 13 ± 0.3 mm; S2, 12 ± 2 mm) are similar to those reported by Lee et al [19] (S1: 14 ± 4 mm; S2 11 ± 3 mm) and larger than those reported by Vanderschot et al [37]. (S1, 8 ± 0.9 mm; S2, 7 ± 3 mm).…”
Section: Discussionsupporting
confidence: 90%
“…Sacral dysmorphism has been a concern when inserting iliosacral screws owing to the reduced volume within the sacral ala for screw placement. Anatomic studies by Gardner et al and Lee et al have shown that there is up to 1 cm of bone available for screw insertion in 96% of patients with sacral dysmorphism . The results presented here support these conclusions as sacral dsymorphism was not associated with mal‐positioned screws.…”
Section: Discussionsupporting
confidence: 84%
“…In contrast to previous studies, we aligned the 3D model of the pelvis manually in the lateral view to assess the maximal possible diameter. Other studies have conducted measurements on CT images with the problem of CT reconstruction addressed above, created 3D models with automatic segmentation, risking incomplete or imprecise segmentation of cortical bone (especially in elderly patients), or aligned the pelves automatically . Due to some pelvic asymmetry, in our opinion, the latter often results in a possible underestimation of the corridor diameter.…”
Section: Discussionmentioning
confidence: 99%
“…A “dysmorphic” phenotype of the sacrum has been defined, which offers limited space for implant positioning within the upper sacrum. The percentage of sacra not allowing S1 trans‐sacral implants has been reported to be 11–53%, and is more often present in females and certain ethnicities . In contrast, pelves with “dysmorphic” sacra or small trans‐sacral corridor S1 offer more safe space in S2, with one fourth of these pelves presenting a trans‐sacral corridor in S3 .…”
mentioning
confidence: 99%